1996
DOI: 10.1007/bf00417945
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci controlling resistance to gray leaf spot disease in maize

Abstract: Breeding maize for gray leaf spot (GLS) resistance has been hindered by the quantitative nature of the inheritance of GLS resistance and by the limitations of selection under less than optimumal disease pressure. In order to identify the quantitative trait loci (QTLs) controlling GLS resistance, a cross was made between B73 (susceptible) and Va14 (resistant) to generate a large F2 population. Six GLS disease assessments were made throughout the disease season for over 1000 F2 plants in 1989, and for 600 F2-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The QTL with the allele associated with GLS resistance derived from CML444 in bin 4.08 was identified in four environments as well as the joint GLS QTL (Table 2, Additional file 1). Both inbred line VP31 and its progenitor VO163Y have a QTL in this bin [7,24], which also overlap with QTL reported by Bubeck et al [21] and Saghai Maroof et al [22]. The GLS QTL with the SC Malawi allele associated with resistance in bin 7.02/7.03 overlaps with QTL from four studies [3,21,23,26] (Additional file 1).…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…The QTL with the allele associated with GLS resistance derived from CML444 in bin 4.08 was identified in four environments as well as the joint GLS QTL (Table 2, Additional file 1). Both inbred line VP31 and its progenitor VO163Y have a QTL in this bin [7,24], which also overlap with QTL reported by Bubeck et al [21] and Saghai Maroof et al [22]. The GLS QTL with the SC Malawi allele associated with resistance in bin 7.02/7.03 overlaps with QTL from four studies [3,21,23,26] (Additional file 1).…”
Section: Resultssupporting
confidence: 63%
“…Detection of QTL for GLS resistance has been reported to be variable from site to site and season to season [21]. For example, Saghai Maroof et al [22] identified three QTL that were consistent in F2 and F3 generations and seasons, but another two QTL that were not. The use of a RIL population in our study allowed testing in multiple environments, which gave confidence in the detected QTL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations